An evaluation of the sporicidal activity of ozone. - Rickloff, J R (1987)
This study was undertaken to determine the feasibility of sterilizing surfaces with ozone-saturated water by the methods of the Association of Official Analytical Chemists (AOAC). Initially, it was determined that there was no apparent difference in ozone resistance between spores of Bacillus subtilis and Clostridium sporogenes when they are suspended in water. Both species were inactivated by a 10-min exposure at ambient temperature. Resistance was increased when the spores were dried on AOAC carriers. Viable organisms were recovered after an exposure of 40 min at ambient temperature. An increase in the reactor water temperature to 60 degrees C did not improve the effectiveness of the ozone in sterilizing AOAC carriers. Dried spores of C. sporogenes were more resistant than B. subtilis spores because of a greater accumulation of organic matter on the carriers. No significant sporicidal activity was demonstrated after 40 min for spores of either species when they were inoculated on silk suture loops. The data suggest that organic loading and poor ozone penetrability are key factors in effecting the ability of ozone to sterilize surfaces rapidly.